Visita a los GADS parroquiales de San Simón y San Lorenzo - Llivi Ruilova, Danny Vicente (2023)
The visit to the parish GADs of San Simón and San Lorenzo was carried out, as part of the activities of the project to link the Risk career of the Faculty of Health and Human Sciences of the UEB, called: “ Update of the Cultural Heritage of the Guaranda Canton”; under the tutelage of Engineer Carlos Ocampo; with the technical support of Architect Adriana Barragán and Engineer Alejandra Benavides; As counterpart to the GADs, the Architects Marco Bonilla and Rodrigo Goyes, Coordination of the Planning Department, participated.